Establishment of Social Identity Among the Youth within the K-Pop Community: Netnography Analysis - Nurudin, Nurudin; Sukmana, Oman; Salviana DS, Vina; Wahyudi, Wahyudi (Technium Social Sciences Journal, 2025)
Korean culture has significantly influenced Indonesia’s youth’s beliefs, attitudes, and behaviours. This study investigates the emergence of new social identities resulting from the influence of K-pop music on the nctzenmalang.idn community. This study employs a qualitative methodology and netnographic research to investigate the development of new social identities among the youth of the nctzenmalang.idn community. The netnographic data in this study is derived from digital community documentation and augmented by interviews. This study’s findings indicate that K-pop idols contribute to forming the K-popers community’s new social identity. K-popers constitute a community of enthusiasts of Korean music entertainment and have evolved to effect changes in their social milieu. The transformation of identity prompted the rise of new imperialism, influenced by cultural shifts and the impact of K-pop music. This study advances contemporary research and social identity theories in the digital age, as online fandom communities shape and impact social identity.